Hubungan Antara Penyesuaian Diri Dan Dukungan Sosial Terhadap Stres Lingkungan Pada Santri Baru - Handoko, Oki Tri (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstractÂ This study aimed to investigate the relationship between social support and adjustment to stress environments in new students at boarding school. The method of research using quantitative methods. The data collection methods using scale adjustment and social support scale and environmental stress. The method of data analysis using analytical techniques regresi.Subjek new research is students who take lessons at the boarding school. Junior secondary school (Madrasah Tsanawiyah) class one and senior high school (Madrasah Aliyah) class one. The experiment was conducted with the subject of as many as 46 people by using populatif. The data analysis technique used is the two-predictor analysis techniques with the help of Statistical Product and Service Solutions (SPSS) for Windows 19.0. Keywords: Adjustment, Social Support, Stress Environment.Â